Analisis Peran Biro Umum Sekretariat Daerah Provinsi DKI Jakarta atas Kebutuhan Pengguna Gedung pada Pemeliharaan dan Perawatan Mekanikal Elektrikal Gedung Kantor Balai Kota Provinsi DKI Jakarta - Baskoro Setiyo; Tuswoyo Tuswoyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The purpose of this research is to identify the role of the general bureau of Jakarta Provincial Secretariat to the needs of building users on mechanical electrical maintenance of Jakarta City Hall Office. This research uses qualitative descriptive method to describe and explain the existing phenomena in detail by using interview as its supporting instrument. This research shows that the general bureau is doing well. It not only performs building maintenance, but also communicates properly, shows effective personality and well personal grooming for professional appearance. Another role of a general bureau officer in carrying out an official event is as a coordinator not only for herself/himself, but also for all related parties. A general bureau officer must be able to establish communication with related parties and act as a mediator, a coordinator, and a manager who organizes the events well. Service is a dynamic state associated with products, services, people, processes, and the environment where its quality assessment is determined at the time it is provided. Assessing service quality considers the role of the community as the service recipient and the officers as the service provider.